The roles of juvenile hormone, insulin/target of rapamycin, and ecydsone signaling in regulating body size inDrosophila - Mirth, Christen Kerry (2015)
Understanding how organisms regulate their body size has interested biologists for decades. Recent work has shown that both insulin/target of rapamycin (TOR) signaling and the steroid hormone ecdysone act to regulate rates of growth and the duration of the growth period in the fruit fly, Drosophila melanogaster. Our recent work has uncovered a third level of interaction, whereby juvenile hormone (JH) regulates levels of both ecdysone and insulin/TOR signaling to control growth rates. These studies highlight a complex network of interactions involved in regulating body and organ size.